Essentially Quasi-Invertible Submodules and Essentially Quasi-Dedekind Modules - Hadi, I.M-A; Ghawi, Th. Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Let R be a commutative ring with identity . In this paper we study the concepts of essentially quasi-invertible submodules and essentially quasi-Dedekind modules as a generalization of quasi-invertible submodules and quasi-Dedekind modules . Among the results that we obtain is the following : M is an essentially quasi-Dedekind module if and only if M is aK-nonsingular module,where a module M is K-nonsingular if, for each , Kerf â‰¤e M implies f = 0 .